A 0.6-V pseudo-differential OTA with switched-opamp technique for low power applications. (August 2019) - Wang, Jingyu; Li, Yongyuan; Zhu, Zhangming
Abstract: A low-voltage, pseudo-differential OTA is presented in this study for power-effective applications. The cross-coupled common-mode feedforward (CMFF) technique is proposed to improve the CMRR performance and double transconductance of pseudo-differential OTA with the same power consumption as the conventional one. Implemented under the supply voltage of 0.6 V, the designed OTA, which converts the single-ended signal into the fully differential signal, is used as the input buffer of ADC. Considering the particularity of ADC application, switched-opamp (SO) technology is designed to turn off amplifier partly for compromising high power efficiency and short start time. Implemented in the 0.18-μm standard CMOS process, the OTA occupies an active chip area of 0.05 mm 2 and provides the settling time of 310 ns with 0.1% accuracy for 0.6 Vpp output step. The measured input noise spectrum density is −147 dBv/ Hz (45 nv / Hz ) @ 25 MHz. The output-referred integrated noise voltage is 485 μV from 20 Hz to 25 MHz.